2006
DOI: 10.1117/12.647412
|View full text |Cite
|
Sign up to set email alerts
|

Transient optical angular momentum effects and atom trapping in multiple twisted beams

Abstract: Theoretical work has already established the existence of a light-induced torque acting on the centre of mass of an atom, ion or molecule immersed in twisted light, where the transition frequency is suitably detuned from that of the twisted light beam. The twisted beam carries l units of orbital angular momentum per photon, and the steady-state saturation form of the torque is also determined by the width of the upper state in the atomic transition. It has been shown that, to leading order, the transfer of orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The effects of structured light on atom dynamics, in both its forms, namely the gross motion and the internal motion have been thoroughly investigated (see references ( [129][130][131][132][133][134][135][136]). These investigations have shown that the interaction of light carrying OAM with atoms introduces new significant features, namely that (i) there is, in addition to translational effects, a light-induced torque which causes a rotational motion of the atoms about the beam axis, and (ii) there are characteristic regions of maximum and minimum intensity in the beam cross-section.…”
Section: Radiation Pressure Forces and Torquesmentioning
confidence: 99%
“…The effects of structured light on atom dynamics, in both its forms, namely the gross motion and the internal motion have been thoroughly investigated (see references ( [129][130][131][132][133][134][135][136]). These investigations have shown that the interaction of light carrying OAM with atoms introduces new significant features, namely that (i) there is, in addition to translational effects, a light-induced torque which causes a rotational motion of the atoms about the beam axis, and (ii) there are characteristic regions of maximum and minimum intensity in the beam cross-section.…”
Section: Radiation Pressure Forces and Torquesmentioning
confidence: 99%
“…Against this background, the theoretical and technological developments that have recently led to the production of structured laser light introduce another tier of possibilities associated with orbital angular momentum (OAM) content [10][11][12][13][14]. The intricate wavefront structures of Laguerre-Gaussian, Bessel, and Mathieu light beams, for example, allow the production of force fields and torques that have no counterpart in conventional optical beams.…”
mentioning
confidence: 99%
“…10 Vector field representation of the director orientation of the twisted nematic liquid crystal before application of the twisted light. The orientation at the boundaries z = 0 (bottom) and z = d (top) are fixed as described in text.…”
mentioning
confidence: 99%